Stability analysis and modelling of underground excavations in fractured rocks - Zhu, Weishen (Elsevier geo-engineering book series ;, 2004)
* Provides practical solutions to the challenge of modeling and analyzing rock masses * Consolidates a wealth of previously published technical papers on the subject and introduces previously unseen material This authoritative title is a key reference for any Geo-engineer. Rock masses differ considerably from man-made materials, and their properties can vary with location, direction and time. As a result there is a critical need to capture these variations via modeling and analysis. Zhu and Zhao provide an expert introduction to the techniques and analytical methods needed for studying underground excavations in fractured rock masses. The book brings together previously published and new material to provide a comprehensive and up-to-date reference. * Provides practical solutions to the challenge of modeling and analyzing rock masses * Consolidates a wealth of previously published technical papers on the subject and introduces previously unseen material.